Collaborative Care for Depressed Patients With Chronic Medical Conditions: A Randomized Trial in Puerto Rico - Vera, Mildred (2010)
OBJECTIVE: This study examined whether a collaborative care model for depression would improve clinical and functional outcomes for depressed patients with chronic general medical conditions in primary care practices in Puerto Rico. METHODS: A total of 179 primary care patients with major depression and chronic general medical conditions were randomly assigned to receive collaborative care or usual care. The collaborative care intervention involved enhanced collaboration among physicians, mental health specialists, and care managers paired with depression-specific treatment guidelines, patient education, and follow-up. In usual care, study personnel informed the patient and provider of the diagnosis and encouraged patients to discuss treatment options with their provider. Depression severity was assessed with the Hopkins Symptom Checklist; social functioning was assessed with the 36-item Short Form. RESULTS: Compared with usual care, collaborative care significantly reduced depressive symptoms and improved social functioning in the six months after randomization. Integration of collaborative care in primary care practices considerably increased depressed patients' use of mental health services. CONCLUSIONS: Collaborative care significantly improved clinical symptoms and functional status of depressed patients with coexisting chronic general medical conditions receiving treatment for depression in primary care practices in Puerto Rico. These findings highlight the promise of the collaborative care model for strengthening the relationship between mental health and primary care services in Puerto Rico.